2020
DOI: 10.1681/asn.2020050639
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Infection in Kidney Transplant Recipients: Disease Incidence and Clinical Outcomes

Abstract: BackgroundCOVID-19 has been associated with high morbidity and mortality in kidney transplant recipients. However, risk factors for COVID-19 disease in patients with kidney transplants remain poorly defined.MethodsWe enrolled patients who underwent kidney transplantation and were actively followed up in two hospitals in Paris on March 1st, 2020. Patients were screened for baseline and transplant characteristics, functional parameters, comorbidities, and immunosuppressive therapies. COVID-19 disease was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
232
9
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(254 citation statements)
references
References 16 publications
5
232
9
8
Order By: Relevance
“…Likewise, accounting for the higher proportion of transplant recipients who are male, the incidence of COVID-19 after kidney transplantation also appears to be similar in both sexes. 1 However, after controlling for age and comorbidities, COVID-19-attributable mortality rates in the general population are 1.5 to 2.0-fold higher in males than females. 3 In contrast, while kidney transplantation has been associated with as much as a 10-fold higher mortality with COVID-19 disease compared with the general population, 2 no consistent sex differences in COVID-19-related mortality have been observed in kidney transplant recipients.…”
Section: Impact Of Covid-19 In Kidney Transplant Recipientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, accounting for the higher proportion of transplant recipients who are male, the incidence of COVID-19 after kidney transplantation also appears to be similar in both sexes. 1 However, after controlling for age and comorbidities, COVID-19-attributable mortality rates in the general population are 1.5 to 2.0-fold higher in males than females. 3 In contrast, while kidney transplantation has been associated with as much as a 10-fold higher mortality with COVID-19 disease compared with the general population, 2 no consistent sex differences in COVID-19-related mortality have been observed in kidney transplant recipients.…”
Section: Impact Of Covid-19 In Kidney Transplant Recipientsmentioning
confidence: 99%
“…The estimated incidence of SARS-CoV-2 infection and COVID-19 disease in patients on dialysis and with kidney transplants exceeds that of the general population by as much as 15-fold. 1 The risk of complications and death associated with COVID-19 is also considerably higher among kidney transplant recipients. 2 Reasons for the observed differences between transplant recipients and the general population may be attributed to multiple comorbidities, and the suppressed immune system in these vulnerable patients.…”
Section: Impact Of Covid-19 In Kidney Transplant Recipientsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Kidney transplant recipients (KTRs) are particularly vulnerable to higher morbidity and mortality in the setting of COVID-19 infection due to the higher incidence of comorbid conditions compared to the general population as well as a depressed immune state. 3,14 In a prospective study consisting of 1,216 KTRs, the incidence of COVID-19 infection was found to be 5% with a mortality rate of 24% among COVID-19-positive patients compared to a mortality rate ranging from 1% to 5% in the general population. 14 Fever is the most common reported symptom of COVID-19 in KTRs, followed by cough, dyspnea, and gastrointestinal symptoms; some patients present with mild or atypical symptoms such as conjunctivitis and a normal white blood cell count.…”
Section: Covid19 and Kidney Transplant Recipientsmentioning
confidence: 99%
“…14 Fever is the most common reported symptom of COVID-19 in KTRs, followed by cough, dyspnea, and gastrointestinal symptoms; some patients present with mild or atypical symptoms such as conjunctivitis and a normal white blood cell count. [14][15][16][17] Thus, mild and atypical symptoms should prompt testing for COVID-19 in KTRs.…”
Section: Covid19 and Kidney Transplant Recipientsmentioning
confidence: 99%